Extending the Technology Acceptance Model (TAM) to explore customer's behavioral intention to use Self-Service Technologies (SSTs) in Chinese budget hotels - Ke Yang; Jeong-gil Choi; Jellna Chung (Global Business & Finance Review (GBFR), 2021)
Purpose: With the development and increasing adoption of the Internet in the early 21st century, SSTs (Self-Service Technologies) rapidly permeated all aspects of life. Many service providers in China are adopting a wide range of SSTs. This is mainly because they think SSTs improve customer service, increase productivity, and reduce costs. Problem is how potential customers perceive the SSTs and behave. Design/methodology/approach: This study hypotheses that the original TAM and extended TAM would not apply to customers using SSTs in Chinese budget hotels. All the relationships among variables on these models were tested by using a Structural Equation Model (SEM). Findings: Results proved that all of the relationships on the original TAM do apply to customers using SSTs in Chinese budget hotels. However, the extended TAM does not fit into this particular market. Research limitations/implications: This study examined the TAM with perceived risk and perceived playfulness to determine the factors influencing customers' behavioral intention to use SSTs in budget hotels. This approach is likely to ensure a stable theory development. Hence, the proposed model makes an important contribution to the emerging literature on SSTs. Moreover, this study originally hypothesized perceived risk affected on customers' satisfaction and behavioral intention to use SSTs in Chinese budget hotels. But it is rejected. Originality/value: This study offers empirical evidence and makes contribution to future research related to further developing an understanding of the relationship between perceived risk and SSTs adoption.
Keywords: 650; SSTs; TAM; Perceived risk; Perceived playfulness; Chinese budget hotel